2021
DOI: 10.1186/s10020-021-00338-8
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cell-derived extracellular vesicles transfer miR-182-5p and promote breast carcinogenesis via the CMTM7/EGFR/AKT axis

Abstract: Background Extracellular vesicles (EVs) derived from tumor cells are implicated in the progression of malignancies through the transfer of molecular cargo microRNAs (miRNAs or miRs). We aimed to explore the role of EVs derived from breast cancer cells carrying miR-182-5p in the occurrence and development of breast cancer. Methods Differentially expressed miRNAs and their downstream target genes related to breast cancer were screened through GEO and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…EVs contain bioalogical molecules, such as nucleic acids (DNA, mRNA, microRNA, and other noncoding RNAs), proteins (receptors, transcription factors, enzymes, and extracellular matrix proteins), and lipids that can influence target cells such as brain endothelial cells [47,48]. Several studies already described the composition of the EVs for both the parental cell line MDA-MB-231 [49,50] and the brain-seeking subline MDA-MB-231-BR [51] to demonstrate a possible EV-dependent brain-metastatic-specific effect. Rodrigues et al reveal only twenty proteins to be differentially expressed in brain-seeking breast cancer cell EVs (MDA-MB-231-BR) compared to the corresponding parental cell line EVs (MDA-MB-231).…”
Section: Discussionmentioning
confidence: 99%
“…EVs contain bioalogical molecules, such as nucleic acids (DNA, mRNA, microRNA, and other noncoding RNAs), proteins (receptors, transcription factors, enzymes, and extracellular matrix proteins), and lipids that can influence target cells such as brain endothelial cells [47,48]. Several studies already described the composition of the EVs for both the parental cell line MDA-MB-231 [49,50] and the brain-seeking subline MDA-MB-231-BR [51] to demonstrate a possible EV-dependent brain-metastatic-specific effect. Rodrigues et al reveal only twenty proteins to be differentially expressed in brain-seeking breast cancer cell EVs (MDA-MB-231-BR) compared to the corresponding parental cell line EVs (MDA-MB-231).…”
Section: Discussionmentioning
confidence: 99%
“…Several functional studies in different entities have shown that miR-183-5p, miR-182-5p, miR-221-3p and the miR-17-92 cluster induce angiogenesis when taken up by epithelial or endothelial cells. This was achieved through the inhibition of factors as FOXO1 ( 71 ), CMTM7 ( 69 ), VASH1 ( 17 ), THBS2 ( 73 ), SOCS3 ( 75 ), PIK3R1 ( 76 ), TSP-1 and CTGF ( 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence points to the role of tumor-derived extracellular vesicles in tumor angiogenesis of breast cancer. Lu et al recently reported that extracellular vesicles derived from breast cancer cells are highly enriched with miRNA-182-5p which enhanced proliferation and migration of endothelial cells in vitro and angiogenesis and metastasis of breast cancer in vivo (Lu et al, 2021). Microvesicles rich in a special VEGF isoform activated VEGFR and induced angiogenesis while being resistant to bevacizumab (Feng et al, 2017).…”
Section: Micrornas and Extracellular Vesiclesmentioning
confidence: 99%